The Relationship between Perceived Organizational Support and Work Engagement in Police Officers - Putri Hardiyanti, Afrillia; Prabandini Mulyana, Olievia (Jurnal Ilmiah Sumber Daya Manusia, 2026)
This study aims to determine the correlation between Perceived Organizational Support and Work Engagement among members of the Indonesian National Police (POLRI). This study applied a quantitative correlational approach with 150 respondents. Data analysis was conducted using descriptive statistics and the Spearman correlation test. The results showed that perceived organizational support had a positive and significant relationship with the Work Engagement of Polri members (r = 0.543; p < 0.001). Members who perceived higher levels of support tended to be more engaged in their duties. The support was manifested through fair treatment, attention to welfare, and rewards for performance. Theoretically, these findings strengthen the Social Exchange Theory and the Job Demands-Resources Model, which emphasize the role of organizational support as a crucial resource in maintaining motivation and Work Engagement, especially in high-pressure professions such as the police profession. From a practical perspective, this study highlights the importance of strengthening perceived organizational support in the human resource policies and management of the Indonesian National Police to maintain officers’ Work Engagement and professionalism.